Basic Behavioral Processes Involved in Procrastination - Zentall, Thomas R. (Frontiers in Psychology, 2021)
Procrastination involves an irrational putting off of engaging in a course of action, in spite of expecting to be worse off for the delay. I suggest that to understand the processes underlying procrastination one should examine its relation to several behavioral procedures that have been studied in humans and other animals. For example, in delay discounting, smaller rewards that come sooner are often preferred over larger rewards that come later. In the context of delay discounting, procrastination can be viewed as the preference for an immediate competing activity over the delay to work on a required task. Another process similar to procrastination can be seen in free operant, temporal avoidance (or Sidman avoidance) in which an animal will receive a shock (a deadline not met) if an interval passes without a specified response (task completion). Once animals learn about the interval, they often procrastinate by waiting until the interval has almost passed before responding. Finally, research with animals suggests that the persistence of procrastination may involve a form of negative reinforcement associated with the sudden decline in anxiety or fear (relief) when the task is completed prior to the deadline. Research with animals suggests that the mechanisms responsible for human procrastination may involve systems that derive from several procedures known to produce similar behavior animals.